Evaluating Bohm's quantum force in the scattering process by a classical potential. (5th February 2021) - Santana, W S; Cruz, C; Lima, E; Prudente, F V
Abstract: In this work, we show an application of the de Broglie–Bohm quantum theory of motion (QTM) as a powerful tool for evaluating Bohm's quantum force in the scattering process of a Gaussian wavepacket by a classical Eckart potential. Our results show that in the absence of a classical potential, the system experiences quantum effects arising from an effective force, intrinsically related to the existence of the wavepacket itself. In contrast, in the scattering by the classical potential, it experiences a quantum force effect even in the absence of any classical force, reinforcing the fact that potentials can act without classical force fields. Thus, this application could be useful to introduce QTM, through the discussion of the concept of Bohm's quantum force, as a classroom working tool instead of merely an alternative interpretation of the quantum theory.